The Impact of Lowering the Age Limit for Presidential Elections on Political Participation in Indonesia - Amalia, Hilda Vivi (Journal of Current Research In Multidisciplinary, 2023)
This research aims to explain the impact of lowering the age limit for presidential elections on political participation in Indonesia. The data used in this research are data on Indonesian political history, data on changes in the age limit for presidential elections, and data on political participation in Indonesia. The population in this research is all Indonesians who have the right to elect candidates for president and vice president in Indonesia. Samples will be selected through a random sampling method. This research uses qualitative data with a case study method. The data analysis method in this research is the qualitative content analysis method. The research results show that lowering the age limit for presidential elections can have a positive impact on political participation in Indonesia. The positive impact is improving the quality of candidates, increasing community political participation, increasing the use of technology and innovation, improving government performance, and improving political sustainability. In this case, efforts need to be made to develop the younger political generation and develop political competence in Indonesia to present it in the general election process (presidential election) and improve political performance in Indonesia.